Faktor-Faktor yang Mempengaruhi Return Saham pada Perusahaan yang Tercatat pada Indeks LQ-45 - Nazilah, Hikmatun; Damayanti, Damayanti (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
This study aims to analyze the effect of Debt to Equity Ratio, Return on Equity and Earning per Share on Stock Returns in companies listed on the LQ-45 Index on the Indonesia Stock Exchange. The population used in this study were LQ-45 companies listed on the IDX during the 2017-2021 period, with a sample of 10 companies and a total of 50 observations. Analysis data using multiple linear regression analysis. The results of the study, it shows that the Debt to Equity Ratio has a significant positive effect on Stock Returns, Return on Equity has an insignificant positive effect on stock returns, and Earning per Share has a not significant positive effect on stock returns. The results of the determination test show an adjusted R² value of 0.71, which means that the Debt to Equity Ratio, Return on Equity and Earning per Share variables are able to explain the Stock Return variable of 7.1% while the remaining 92.9% is explained by other factors that are not included in the regression model. Keywords: Stock Return, Debt to equity ratio, Return on Equity and Earning per Share.